A controlled trial of HNSCC patient‐derived xenografts reveals broad efficacy of PI3Kα inhibition in controlling tumor growth. Issue 8 (18th December 2018) - Ruicci, Kara M.; Meens, Jalna; Sun, Ren X.; Rizzo, Giananthony; Pinto, Nicole; Yoo, John; Fung, Kevin; MacNeil, Danielle; Mymryk, Joe S.; Barrett, John W.; Boutros, Paul C.; Ailles, Laurie; et al.
Abstract : Head and neck squamous cell carcinomas (HNSCCs) frequently harbor alterations in the PI3K/AKT/mTOR signaling axis, particularly in the PIK3CA gene. PI3K‐targeted agents have therefore gained considerable preclinical and clinical interest as emerging therapies for HNSCC. Identification of predictive biomarkers of response would advance the clinical application of PI3K‐targeted drugs for patients, in order to achieve maximal benefit. To date, studies of drug biomarkers have largely focused on screening cell lines, with much more limited in vivo testing, usually only as validation. This approach has rarely enabled accurate predictions of clinical efficacy. Recently, clinical trials of PDX models (PDX clinical trials) have been introduced as a preclinical approach to interrogate interpatient response heterogeneity. Already, PDX clinical trial responses have been demonstrated to correlate closely with patient outcomes. Here, using both an HNSCC specific, 28‐cell line panel and a PDX clinical trial of 80 xenografts derived from 20 unique HNSCC tumors, we systematically examine patterns of response to PI3K inhibition in HNSCC. We find EGFR, AKT1 and CSMD1 copy number aberrations, but not PIK3CA mutations, to be associated with responsiveness to PI3K‐targeted drugs. Further, we reveal PI3Kα inhibition to be almost globally tumoristatic in HNSCC xenografts regardless of PIK3CA mutational status, emphasizing its potential as a stabilizing neoadjuvant therapy for HNSCC patients. Abstract : What's new? To date, profiling of anti‐cancer therapeutics in head and neck squamous cell carcinoma (HNSCC) cell lines has rarely resulted in accurate predictions of clinical efficacy. Using patient‐derived xenograft (PDX) models, which more closely replicate both intra‐ and inter‐tumor heterogeneity, targeted therapeutics can be interrogated in a more clinically‐relevant model. Here, the authors conducted a Phase II‐like trial of genomically‐characterized HNSCC PDXs to examine PI3‐kinase targeting and identified a role for PI3‐kinase inhibition in the neoadjuvant setting.